Distrust in the Balance: The Emergence and Development of Intergroup Distrust in a Court of Law - Bijlsma-Frankema, Katinka; Sitkin, Sim B.; Weibel, Antoinette (Organization science (Providence, R.I.), 2015)
Despite recent attention to trust, comparatively little is known about distrust as distinct from trust. In this paper, we drew on case study data of a reorganized court of law, where intergroup distrust had grown between judges and administrators, to develop a dynamic theory of distrust. We used insights from the literatures on distrust, conflict escalation, and professional–organization relations to guide the analysis of our case data. Our research is consistent with insights on distrust previously postulated, but we were able to extend and make more precise the perceptions and behaviors that make up the elements of the self-amplifying cycle of distrust development, how these elements are related, and the mechanisms of amplification that drive the cycle. To help guide and focus future research, we modeled the process by which distrust emerges and develops, and we drew inferences on how it can be repaired.